Magnetic titanium dioxide composite material for photocatalysis of printing and dyeing wastewater and preparation method thereof

By using a core-shell structure magnetic titanium dioxide photocatalyst supported by chitosan carrier in wastewater treatment, the problem of difficulty in removing organic dyes and titanium dioxide in the prior art is solved, and efficient photocatalytic degradation and magnetic separation and recovery are achieved. Suitable for industrial applications.

CN119386934APending Publication Date: 2025-02-07NORTH CHINA UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411685989.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-24
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove organic dyes in wastewater treatment, and the titanium dioxide photocatalyst is difficult to separate and recover after catalytic reaction, which affects its industrial application.

Method used

A new type of magneto-photocatalyst is prepared by using chitosan as a support and carrying the core-shell structure of magnetic titanium dioxide photocatalyst. By adjusting the ratio of Fe3O4, SiO2, TiO2 and chitosan, the adsorption performance and photocatalytic activity of the catalyst are improved.

Benefits of technology

The efficient photocatalytic degradation effect is achieved, and the degradation efficiency of printing and dyeing wastewater reaches more than 95%. Due to the presence of magnetic materials, the catalyst can be separated and recovered under an external magnetic field, which is suitable for recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386934A_ABST
    Figure CN119386934A_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic titanium dioxide composite material for photocatalysis of printing and dyeing wastewater and a preparation method thereof, titanium dioxide and a magnetic matrix Fe3O4 are compounded, a transition layer SiO2 is added, core-shell type magnetic titanium dioxide is prepared, chitosan is used as a carrier and is loaded, the proportion of Fe3O4 to titanium dioxide needs to be configured, and the magnetic titanium dioxide composite material is prepared. The ratio of chitosan to titanium dioxide also needs to be configured, and the ratio of Fe3O4 to SiO2 is 1: 2, 1: 4 or 1: 6; the addition amount of Fe3O4-coated SiO2 is 8%, 6%, 4% and 2% of TiO2, namely n (Fe3O4-coated SiO2) / n (TiO2) is equal to 0.08, 0.06, 0.04 and 0.02, and the addition amount of chitosan is 5%, 10%, 20% and 50% of Fe3O4-coated SiO2-coated TiO2, namely n (CS) / n (Fe3O4-coated SiO2-coated TiO2) is equal to 0.05, 0.1, 0.2 and 0.5. Chitosan is adopted as a carrier to load a magnetic titanium dioxide composite photocatalyst with a core-shell structure, and the magnetic titanium dioxide composite photocatalyst is used for photocatalytic degradation. The adsorption capacity of the photocatalytic material is improved through chitosan, so that the surface concentration of pollutants on the catalyst is increased, the utilization rate of photo-induced electron-hole pairs is increased, and the photocatalytic performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sewage treatment, in particular to the preparation of a magnetic titanium dioxide composite material, and in particular to a preparation method of a novel magnetic titanium dioxide composite material for photocatalytic printing and dyeing wastewater. Background Art

[0002] As the environmental water pollution problem becomes increasingly serious, especially the water pollution problem caused by organic dyes has become a common concern of countries around the world. Organic dyes have the characteristics of heavy chromaticity, high toxicity, stable existence in nature, and difficulty in degradation. Excessive accumulation in water bodies will block sunlight, not only affecting aquatic organisms, but also causing many diseases in humans. However, many industrial wastewaters cannot effectively remove dyes after primary treatment. If these dyes are discharged into the water without treatment, they will cause great harm to the water environment.

[0003] Common technologies for the treatment of persistent organic pollutants include biological oxidation, physical adsorption, coagulation and sedimentation, but these methods all have some disadvantages. For example, the chemical method has harsh reaction conditions and high treatment costs, the physical method has large treatment equipment and low purification degree, and the biological method is difficult to treat high-concentration, toxic organic wastewater. Photocatalytic technology has received much attention from scholars at home and abroad. From the perspective of energy utilization, it can use sunlight to activate catalysts, undergo redox reactions, degrade organic pollutants, and improve the environment. At present, this technology has shown wide application potential in environmental pollution control such as sewage treatment, air purification, sterilization, and self-cleaning. Titanium dioxide photocatalysts have become the most popular nano-photocatalytic materials in the world because of their high photocatalytic activity, stable chemical properties, strong oxidation ability, wide range of applications, no secondary pollution, low price, and non-toxicity. However, studies have found that after the catalytic reaction is completed, titanium dioxide is difficult to separate and recycle for reuse. Through traditional separation methods such as gravity sedimentation and centrifugal separation, the loss rate is large, the treatment process is complex, and the cost is high, which is not conducive to industrial application.

[0004] At present, one method is to make titanium dioxide into a thin film, and then load it on a carrier such as glass fiber mesh, silicon wafer, activated carbon, zeolite, hollow ceramic ball, etc. to make a supported titanium dioxide photocatalyst. However, due to the relatively large particle size of these carriers, the effective specific surface area of ​​the titanium dioxide photocatalyst is reduced after loading, which affects the adsorption of pollutants and photocatalytic activity, thereby weakening the degradation effect of organic wastewater.

[0005] Another method is to combine nanoparticles with magnetic materials to make core-shell magnetic composite titanium dioxide photocatalysts. This catalyst consists of a magnetic core that gives the system magnetism and a titanium dioxide shell with catalytic activity. After the photocatalytic reaction is completed, it is separated and recovered under the action of an external magnetic field. The core-shell magnetic composite titanium dioxide photocatalyst prepared in this way not only maintains the high specific surface area and photocatalytic activity of titanium dioxide nanoparticles, but is also easy to separate and recover from the reaction system for easy recycling.

[0006] And how to make the photocatalyst have both photocatalytic degradation effect and adsorption effect in sewage treatment? It was found that loading the magnetic titanium dioxide composite photocatalyst on the surface of an adsorbent with adsorption effect can further improve the photocatalytic degradation efficiency, because the addition of the adsorbent makes the pollutants quickly gather around the magnetic titanium dioxide photocatalyst, thereby increasing the degradation rate. Summary of the invention

[0007] In order to solve the above technical problems, chitosan is used as a carrier to load a magnetic titanium dioxide photocatalyst with a core-shell structure, and a new type of magnetic photocatalyst is prepared for the degradation of pollutants. Fe3O4@SiO2@TiO2 and CS have a synergistic effect, which can effectively enhance the catalytic ability of the composite photocatalyst. The addition of chitosan can improve the adsorption performance of the catalyst, and compared with other inorganic carriers and organic carriers, chitosan has better transparency and will not hinder the absorption of photons by titanium dioxide, thereby improving the photocatalytic performance of the material. In summary, the present invention provides a method for preparing a new type of magnetic titanium dioxide composite material with higher photocatalytic activity and easy recycling.

[0008] The present invention is achieved through the following technical solutions:

[0009] A magnetic titanium dioxide composite material for photocatalytic printing and dyeing wastewater is disclosed. Titanium dioxide is compounded with a magnetic matrix Fe3O4 and a transition layer SiO2 is added to prepare a core-shell type magnetic titanium dioxide. Chitosan is used as a carrier to load the titanium dioxide. The ratio of Fe3O4 to titanium dioxide needs to be configured, and the ratio of chitosan to titanium dioxide also needs to be configured. The ratio of Fe3O4 to SiO2 is 1:2, 1:4, and 1:6. The addition amount of Fe3O4@SiO2 is 8%, 6%, 4%, and 2% of TiO2, that is, n(Fe3O4@SiO2) / n(TiO2)=0.08, 0.06, 0.04, and 0.02. The addition amount of chitosan is 5%, 10%, 20%, and 50% of Fe3O4@SiO2@TiO2, that is, n(CS) / n(Fe3O4@SiO2@TiO2)=0.05, 0.1, 0.2, and 0.5.

[0010] Furthermore, the ratio of Fe3O4 to SiO2 is 1:2; the ratio of Fe3O4 to SiO2 is 1:4; the ratio of Fe3O4 to SiO2 is 1:6.

[0011] Furthermore, the amount of Fe3O4@SiO2 added is 8% of TiO2, i.e., n(Fe3O4@SiO2) / n(TiO2)=0.08;

[0012] Furthermore, the amount of Fe3O4@SiO2 added is 6% of TiO2, i.e., n(Fe3O4@SiO2) / n(TiO2)=0.06;

[0013] Furthermore, the amount of Fe3O4@SiO2 added is 4% of TiO2, i.e., n(Fe3O4@SiO2) / n(TiO2)=0.04;

[0014] Furthermore, the amount of Fe3O4@SiO2 added is 2% of TiO2, i.e., n(Fe3O4@SiO2) / n(TiO2)=0.02;

[0015] Furthermore, the amount of Fe3O4@SiO2 added is 2% of TiO2, that is, n(Fe3O4@SiO2) / n(TiO2)=0.02. The amount of chitosan added is 5% of Fe3O4@SiO2@TiO2, n(CS) / n(Fe3O4@SiO2@TiO2)=0.05; the amount of chitosan added is 10% of Fe3O4@SiO2@TiO2, that is, n(CS) / n(Fe3O4@SiO2@TiO2)=0.1; the amount of chitosan added is 20% of Fe3O4@SiO2@TiO2, that is, n(CS) / n(Fe3O4@SiO2@TiO2)=0.2; the amount of chitosan added is 50% of Fe3O4@SiO2@TiO2, that is, n(CS) / n(Fe3O4@SiO2@TiO2)=0.5.

[0016] A method for preparing a magnetic titanium dioxide composite material for photocatalysis of printing and dyeing wastewater comprises the following steps:

[0017] (1) First, weigh an appropriate amount of Fe3O4 and hydrochloric acid (0.1 mol / L) and add them into a beaker;

[0018] (2) ultrasonically treating the mixed solution obtained in step (1) for 10 min, and washing it to neutrality (washing with deionized water);

[0019] (3) Accurately weigh 80 ml of deionized water, 320 ml of anhydrous ethanol, and 4 ml of aqueous ammonia (28%) to obtain a mixed solution and place it in a beaker;

[0020] (4) slowly adding ethyl orthosilicate to the mixed solution obtained in step (3) and reacting at 30° C. for 6 h to obtain a precipitate;

[0021] (5) washing the precipitate obtained in step (4) by centrifugation (washing the product with deionized water and ethanol, respectively), and vacuum drying for 12 h to obtain a precipitate;

[0022] (6) adding the precipitate obtained in step (5) to a mixed solution of 30 ml of hexane and 0.1 ml of deionized water, and adding butyl titanate to a beaker;

[0023] (7) dispersing the sample in the beaker of step (6) by ultrasonication for 1 h to obtain a mixture;

[0024] (8) The mixture obtained in step (7) was transferred to a hydrothermal reactor and reacted at 100° C. for 2 h; the precipitate was collected and washed with hexane three times, and dried at room temperature to obtain a powder;

[0025] (9) calcining the powder obtained in step (8) at 450° C. in a muffle furnace for 5 h to obtain a product;

[0026] (10) Take 50 mL of glacial acetic acid (2%) solution, add 0.2 g of chitosan and stir until it is completely dissolved to obtain a transparent colloidal solution;

[0027] (11) adding the product obtained in step (9) to the transparent colloidal solution and stirring for 10 min;

[0028] (12) placing the solution obtained in step (11) in an ultrasonic oscillator for 20 minutes to obtain a solution;

[0029] (13) adding a certain amount of NaOH-anhydrous ethanol (0.01 mol / L) to the solution obtained in step (12) to adjust the pH to neutral to obtain a colloidal solution;

[0030] (14) Add 4 ml of 25% glutaraldehyde to the colloidal solution obtained in step (13), react at 40° C. for 12 h, and filter and wash to obtain the product;

[0031] (15) vacuum drying the product obtained in step (14) for 6 h to obtain a precipitate;

[0032] (16) The powder obtained in step (15) was calcined in a muffle furnace at 200° C. for 2 h to obtain a product.

[0033] Furthermore, the hydrochloric acid solution in step (1) is 0.1 mol / L;

[0034] Furthermore, the ultrasonic time in step (2) is 10 min.

[0035] Furthermore, the volume fraction of aqueous ammonia in step (3) is 28%.

[0036] Furthermore, the reaction temperature in step (4) is 30°C and the reaction time is 6h;

[0037] Furthermore, the vacuum drying time in step (5) is 12 h;

[0038] Furthermore, the ultrasonication time in step (7) is 1 h.

[0039] Furthermore, the hydrothermal reactor temperature in step (8) should be set to 100°C for 2 hours;

[0040] Furthermore, the muffle furnace calcination temperature in step (9) is 450° C. and the calcination time is 5 h.

[0041] Furthermore, the stirring time of step (11) is 10 min;

[0042] Furthermore, the ultrasonic time of step (12) is 20 min.

[0043] Furthermore, the anhydrous ethanol in step (13) is 0.01 mol / L;

[0044] Furthermore, the vacuum drying time in step (15) is 12 h;

[0045] Furthermore, the muffle furnace calcination temperature in step (16) is 200° C. and the calcination time is 2 h.

[0046] The improved effects of the present invention are as follows: a magnetic titanium dioxide photocatalyst with a core-shell structure is loaded on the surface of chitosan, and the chitosan has good transparency and will not hinder the absorption of photons by titanium dioxide. The obtained new magnetic titanium dioxide composite photocatalytic material Fe3O4@SiO2@TiO2-CS also has adsorption performance, so that it has high photocatalytic degradation ability and excellent magnetic properties, ensuring that it can be magnetically separated, recovered and reused multiple times. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is a schematic diagram of the principle of magnetic titanium dioxide photocatalysis.

[0048] Figure 2 This is the degradation curve of Rhodamine B solution by Fe3O4@SiO2@TiO2 with different Fe3O4@SiO2 addition amounts.

[0049] Figure 3 This is the degradation curve of Rhodamine B solution by Fe3O4@SiO2@TiO2-CS with different chitosan addition amounts.

[0050] Figure 4This is the kinetic curve of Fe3O4@SiO2@TiO2 with different Fe3O4@SiO2 addition amounts to Rhodamine B solution.

[0051] Figure 5 This is the kinetic curve of Fe3O4@SiO2@TiO2-CS with different chitosan addition amounts to Rhodamine B solution. DETAILED DESCRIPTION

[0052] Unless otherwise indicated, implied from the context, or customary in the prior art, the tests and characterization methods used are all current as of the filing date of this application. Where applicable, the contents of any patent, patent application, or publication referred to in this application are incorporated herein by reference in their entirety, and their equivalent patent families are also incorporated by reference, especially the definitions of synthesis techniques, products, and processing designs disclosed in these documents in the art. If the definition of a specific term disclosed in the prior art is inconsistent with any definition provided in this application, the definition of the term provided in this application shall prevail.

[0053] The present invention is a novel magnetic titanium dioxide composite material. The titanium dioxide photocatalyst has the advantages of good photocatalytic activity, stable performance, low cost and non-toxicity, etc., but it is found that it is difficult to separate from the reaction system after the catalytic reaction is completed. Even if it can be effectively separated, it is very easy to lose and the cost is high. Nano titanium dioxide is combined with a magnetic substance to prepare a core-shell type magnetic titanium dioxide composite photocatalyst. This catalyst consists of a magnetic core that gives the system magnetism and a titanium dioxide shell with catalytic activity. After the photocatalytic reaction is completed, it is separated and recovered under the action of an external magnetic field. Chitosan is used as a carrier to load a magnetic titanium dioxide composite photocatalyst with a core-shell structure, and a novel magnetic photocatalyst is prepared for photocatalytic degradation. The adsorption capacity of the photocatalytic material is improved by the adsorption capacity of chitosan, thereby increasing the surface concentration of pollutants on the catalyst, improving the utilization rate of photogenerated electron-hole pairs, and thus improving the photocatalytic performance of the material.

[0054] The present invention will be further described in detail below in conjunction with the accompanying drawings and the following embodiments.

[0055] Example 1

[0056] A new type of magnetic titanium dioxide material is achieved through the following pathways:

[0057] (1) First, weigh 0.4 g Fe3O4 and 200 ml hydrochloric acid (0.1 mol / L) and add them into a beaker.

[0058] (2) The mixed solution of the two was ultrasonically treated for 10 min and washed to neutrality (washed with deionized water).

[0059] (3) Accurately weigh 80 ml of deionized water, 320 ml of anhydrous ethanol and 4 ml of aqueous ammonia (28%) to obtain a mixed solution A and place it in a beaker.

[0060] (4) Slowly add ethyl orthosilicate to the mixed solution A and react at 30° C. for 6 h to obtain a precipitate B.

[0061] (5) The precipitate B was washed by centrifugation (the product was washed with deionized water and ethanol, respectively), and vacuum dried for 12 h to obtain a precipitate C.

[0062] (6) Precipitate C was added to a mixed solution of 30 ml of hexane and 0.1 ml of deionized water, and 1.5 ml of butyl titanate was added and placed in a beaker.

[0063] (7) The sample in the beaker of step (6) is dispersed by ultrasonication for 1 h to obtain a mixture.

[0064] (8) The mixture was transferred to a hydrothermal reactor and reacted at 100°C for 2 h. The precipitate was collected, washed with hexane three times, and dried at room temperature to obtain a powder.

[0065] (9) The powder was calcined in a muffle furnace at 450 °C for 5 h to obtain product C.

[0066] (10) Take 50 mL of glacial acetic acid (2%) solution, add 0.2 g of chitosan and stir until it is completely dissolved to obtain a transparent colloidal solution.

[0067] (11) Add product C to the transparent colloidal solution and stir for 10 min.

[0068] (12) The stirred solution was placed in an ultrasonic oscillator for 20 min to obtain solution D.

[0069] (13) A certain amount of NaOH-anhydrous ethanol (0.01 mol / L) was added to solution D to adjust the pH to neutral to obtain a colloidal solution.

[0070] (14) Add 4 ml of 25% glutaraldehyde to colloidal solution E and react at 40°C for 12 h. Filter and wash to obtain product F.

[0071] (15) The product F was dried under vacuum for 6 h to obtain a precipitate G.

[0072] (16) The precipitate G was calcined in a muffle furnace at 200 °C for 2 h to obtain product H.

[0073] The ratio of Fe3O4 to SiO2 in the novel magnetic titanium dioxide composite material obtained in this embodiment is 1:6, the amount of Fe3O4@SiO2 added is 4% of TiO2, and the amount of chitosan added is 5% of Fe3O4@SiO2@TiO2. According to X-ray diffraction, ultraviolet spectrophotometer, transmission electron microscope and photocatalytic experimental analysis of printing and dyeing wastewater represented by rhodamine B solution under visible light, the magnetic titanium dioxide loaded with chitosan increases the surface concentration of pollutants on the catalyst through the adsorption capacity of chitosan, improves the utilization rate of photogenerated electron-hole pairs, and thus improves the photocatalytic performance of the material. At the same time, after repeated experiments, the degradation efficiency of rhodamine B solution is above 95%, which shows that the photocatalytic stability of the novel magnetic titanium dioxide material is high and can be recycled.

[0074] Example 2

[0075] The ratio of Fe3O4 to SiO2 in the novel magnetic titanium dioxide composite material obtained in this embodiment is 1:6, and the amount of Fe3O4@SiO2 added is 6% of TiO2. Other technical features are the same as those in Example 1. According to X-ray diffraction, ultraviolet spectrophotometer, transmission electron microscope and photocatalytic experimental analysis of printing and dyeing wastewater represented by rhodamine B solution under visible light, the photocatalytic effect of the novel magnetic titanium dioxide material is also better than that of the traditional magnetic titanium dioxide, but with the reduction of the loaded titanium dioxide, the specific surface area is reduced, the number of active sites is reduced, and the photocatalytic efficiency is reduced.

[0076] Example 3

[0077] The ratio of Fe3O4 to SiO2 in the new magnetic titanium dioxide composite material obtained in this embodiment is 1:6, and the amount of Fe3O4@SiO2 added is 8% of TiO2. Other technical features are the same as those in Example 1. According to X-ray diffraction, ultraviolet spectrophotometer, transmission electron microscope and photocatalytic experimental analysis of printing and dyeing wastewater represented by rhodamine B solution under visible light, the photocatalytic effect of the new magnetic titanium dioxide material is also better than that of traditional magnetic titanium dioxide, but with the reduction of the loaded titanium dioxide, the specific surface area is reduced, and the photocatalytic ability is reduced, so the photocatalytic activity is much lower than that of Example 2.

[0078] Example 4

[0079] The ratio of Fe3O4 to SiO2 in the new magnetic titanium dioxide composite material obtained in this embodiment is 1:6, and the amount of Fe3O4@SiO2 added is 2% of TiO2. Other technical features are the same as those in Example 1. According to X-ray diffraction, ultraviolet spectrophotometer, transmission electron microscope and photocatalytic experimental analysis of printing and dyeing wastewater represented by rhodamine B solution under visible light, the photocatalytic effect of the new magnetic titanium dioxide material is also better than that of traditional magnetic titanium dioxide, but with the excessive amount of titanium dioxide loaded, the photocatalytic ability is also reduced, so the photocatalytic activity is reduced compared with Example 1.

[0080] Example 5

[0081] The ratio of Fe3O4 to SiO2 in the new magnetic titanium dioxide composite material obtained in this embodiment is 1:6, the amount of Fe3O4@SiO2 added is 4% of TiO2, and the amount of chitosan added is 10% of Fe3O4@SiO2@TiO2. Other technical features are the same as those in Example 1. According to X-ray diffraction, ultraviolet spectrophotometer, transmission electron microscope and photocatalytic experimental analysis of printing and dyeing wastewater represented by rhodamine B solution under visible light, the photocatalytic effect of the new magnetic titanium dioxide material is also better than that of traditional magnetic titanium dioxide. With the increase of chitosan, the adsorption capacity increases, the pollutants gather rapidly, and the photocatalytic ability improves, so the photocatalytic activity is slightly improved compared with Example 1.

[0082] Example 6

[0083] The ratio of Fe3O4 to SiO2 in the new magnetic titanium dioxide composite material obtained in this embodiment is 1:6, the amount of Fe3O4@SiO2 added is 4% of TiO2, and the amount of chitosan added is 20% of Fe3O4@SiO2@TiO2. Other technical features are the same as those in Example 1. According to X-ray diffraction, ultraviolet spectrophotometer, transmission electron microscope and photocatalytic experimental analysis of printing and dyeing wastewater represented by rhodamine B solution under visible light, the photocatalytic effect of the new magnetic titanium dioxide material is also better than that of traditional magnetic titanium dioxide. With the increase of chitosan, the adsorption capacity increases, the aggregation speed of pollutants is accelerated, and the photocatalytic ability is improved. Therefore, the photocatalytic activity is slightly improved compared with Example 5.

[0084] Example 7

[0085] The ratio of Fe3O4 to SiO2 in the new magnetic titanium dioxide composite material obtained in this embodiment is 1:6, the amount of Fe3O4@SiO2 added is 4% of TiO2, and the amount of chitosan added is 50% of Fe3O4@SiO2@TiO2. Other technical features are the same as those in Example 1. According to X-ray diffraction, ultraviolet spectrophotometer, transmission electron microscope and photocatalytic experimental analysis of printing and dyeing wastewater represented by rhodamine B solution under visible light, the photocatalytic effect of the new magnetic titanium dioxide material is also better than that of traditional magnetic titanium dioxide. With the increase of chitosan, the exposed area of ​​titanium dioxide decreases, so the photocatalytic activity decreases more than that of Example 6.

[0086] As can be seen from Examples 1 to 7, the present invention adjusts the ratio of Fe3O4, silicon dioxide, titanium dioxide and chitosan, and titanium dioxide is used as a photocatalyst. With the increase of titanium dioxide, the activity of the photocatalytic material also increases. The addition of chitosan causes pollutants to quickly gather on the surface of the photocatalyst, improving the utilization rate of electrons and holes, thereby improving the photocatalytic performance of the material. During the experiment, it was found that when the amount of Fe3O4@SiO2 added was 4% of TiO2 and the amount of chitosan added was 20% of Fe3O4@SiO2@TiO2, Fe3O4@SiO2@TiO2-CS had the best photocatalytic effect on rhodamine B, and the effect of improving the photocatalytic performance was the most significant.

[0087] The above description of the embodiments is to facilitate the understanding and application of the present application by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without having to pay creative labor. Therefore, the present application is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the contents disclosed in the present application without departing from the scope and spirit of the present application are within the scope of the present application.

Claims

1. A magnetic titanium dioxide composite material for photocatalysis of printing and dyeing wastewater, characterized in that: Titanium dioxide is compounded with a magnetic matrix Fe3O4 and a transition layer SiO2 is added to prepare a core-shell type magnetic titanium dioxide, which is then loaded with chitosan as a carrier. The ratio of Fe3O4 to titanium dioxide needs to be configured, and the ratio of chitosan to titanium dioxide also needs to be configured. The ratios of Fe3O4 and SiO2 are 1:2, 1:4, and 1:6; the amount of Fe3O4@SiO2 added is 8%, 6%, 4%, and 2% of TiO2, i.e., n(Fe3O4@SiO2) / n(TiO2)=0.08, 0.06, 0.04, and 0.02; the amount of chitosan added is 5%, 10%, 20%, and 50% of Fe3O4@SiO2@TiO2, i.e., n(CS) / n(Fe3O4@SiO2@TiO2)=0.05, 0.1, 0.2, and 0.

5.

2. The magnetic titanium dioxide composite material for photocatalysis of printing and dyeing wastewater according to claim 1, characterized in that: The ratio of Fe3O4 to SiO2 is 1:2; the ratio of Fe3O4 to SiO2 is 1:4; the ratio of Fe3O4 to SiO2 is 1:

6.

3. The magnetic titanium dioxide composite material for photocatalysis of printing and dyeing wastewater according to claim 1, characterized in that: The amount of Fe3O4@SiO2 added is 8% of TiO2, that is, n(Fe3O4@SiO2) / n(TiO2)=0.08; the amount of Fe3O4@SiO2 added is 6% of TiO2, that is, n(Fe3O4@SiO2) / n(TiO2)=0.06; The amount of Fe3O4@SiO2 added is 4% of TiO2, that is, n(Fe3O4@SiO2) / n(TiO2)=0.04; The amount of Fe3O4@SiO2 added is 2% of TiO2, that is, n(Fe3O4@SiO2) / n(TiO2)=0.02; The amount of Fe3O4@SiO2 added is 2% of TiO2, that is, n(Fe3O4@SiO2) / n(TiO2)=0.

02.

4. The magnetic titanium dioxide composite material for photocatalysis of printing and dyeing wastewater according to claim 1, characterized in that: The amount of chitosan added is 5% of Fe3O4@SiO2@TiO2, n(CS) / n(Fe3O4@SiO2@TiO2)=0.05; the amount of chitosan added is 10% of Fe3O4@SiO2@TiO2, that is, n(CS) / n(Fe3O4@SiO2@TiO2)=0.1; the amount of chitosan added is 20% of Fe3O4@SiO2@TiO2, that is, n(CS) / n(Fe3O4@SiO2@TiO2)=0.2; the amount of chitosan added is 50% of Fe3O4@SiO2@TiO2, that is, n(CS) / n(Fe3O4@SiO2@TiO2)=0.

5.

5. A method for preparing the magnetic titanium dioxide composite material for photocatalysis of printing and dyeing wastewater according to any one of claims 1 to 4, characterized in that: The steps include: (1) First, weigh an appropriate amount of Fe3O4 and hydrochloric acid (0.1 mol / L) and add them into a beaker; (2) ultrasonically treating the mixed solution obtained in step (1) for 10 min, and washing it to neutrality (washing with deionized water); (3) Accurately weigh 80 ml of deionized water, 320 ml of anhydrous ethanol, and 4 ml of aqueous ammonia (28%) to obtain a mixed solution and place it in a beaker; (4) slowly adding ethyl orthosilicate to the mixed solution obtained in step (3) and reacting at 30° C. for 6 h to obtain a precipitate; (5) washing the precipitate obtained in step (4) by centrifugation (washing the product with deionized water and ethanol, respectively), and vacuum drying for 12 h to obtain a precipitate; (6) adding the precipitate obtained in step (5) to a mixed solution of 30 ml of hexane and 0.1 ml of deionized water, and adding butyl titanate to a beaker; (7) dispersing the sample in the beaker of step (6) by ultrasonication for 1 h to obtain a mixture; (8) The mixture obtained in step (7) was transferred to a hydrothermal reactor and reacted at 100° C. for 2 h; the precipitate was collected and washed with hexane three times, and dried at room temperature to obtain a powder; (9) calcining the powder obtained in step (8) at 450° C. in a muffle furnace for 5 h to obtain a product; (10) Take 50 mL of glacial acetic acid (2%) solution, add 0.2 g of chitosan and stir until it is completely dissolved to obtain a transparent colloidal solution; (11) adding the product obtained in step (9) to the transparent colloidal solution and stirring for 10 min; (12) placing the solution obtained in step (11) in an ultrasonic oscillator for 20 minutes to obtain a solution; (13) adding a certain amount of NaOH-anhydrous ethanol (0.01 mol / L) to the solution obtained in step (12) to adjust the pH to neutral to obtain a colloidal solution; (14) Add 4 ml of 25% glutaraldehyde to the colloidal solution obtained in step (13), react at 40° C. for 12 h, and filter and wash to obtain the product; (15) vacuum drying the product obtained in step (14) for 6 h to obtain a precipitate; (16) The powder obtained in step (15) was calcined in a muffle furnace at 200° C. for 2 h to obtain a product.

6. The preparation method according to claim 5, characterized in that: The hydrochloric acid solution in step (1) is 0.1 mol / L; The ultrasonic time in step (2) is 10 min. The volume fraction of aqueous ammonia in step (3) is 28%.

7. The preparation method according to claim 5, characterized in that: The reaction temperature in step (4) is 30°C and the reaction time is 6h; The vacuum drying time of step (5) is 12h; The ultrasonic time of step (7) is 1 h.

8. The preparation method according to claim 5, characterized in that: The hydrothermal reactor temperature in step (8) should be set to 100°C for 2 hours; The muffle furnace calcination temperature of step (9) is 450° C. and the calcination time is 5 h.

9. The preparation method according to claim 5, characterized in that: The stirring time of step (11) is 10 min; The ultrasonic time of step (12) is 20 min.

10. The preparation method according to claim 5, characterized in that: The anhydrous ethanol in step (13) is 0.01 mol / L; The vacuum drying time of step (15) is 12h; The muffle furnace calcination temperature of step (16) is 200° C. and the calcination time is 2 h.

Citation Information

Cited By

  • Efficient decolorizing agent for printing and dyeing wastewater and decolorizing treatment method

    CN120644248A